The problems of limit load analysis and optimization using equilibrium finite elements - Kalanta, Stanislovas (Journal of Civil Engineering and Management, 1996)
The equilibrium dual discrete mathematical models of the problems of limit load analysis and optimization are investigated in the article. These models are presented in terms of static and kinematic formulation using equilibrium finite elements. In these mathematical models the possible discontinuities of displacement velocities are evaluated and the velocity of energy dissipation is estimated not only within the volume of finite elements, but at the plastic surfaces between elements. At first, on the basis of the energy principle of the maximum external power [1,2] the general mathematical models (3) and (7) of static formulation of limit load analysis and optimization problems are created. In these models the yield conditions are controlled not only within the volume, but also at the surfaces of finite elements. The equilibrium finite elements and interpolation functions of strains (9) are used for discretization of these models. The constancy of external power is taken as the optimum criterion. The discrete expressions of fundamental relationships—equilibrium and geometric equations, yield conditions (10)-(12) for finite element and (14)-(17) for the discrete model of a body are developed. The discrete expressions of yield conditions are given using the classic collocation methods: collocation at the point, collocation at the sphere (element) and Bubnov-Galiorkin’s collocation method [11,12]. The equilibrium equations of discrete structure are developed on the basis of virtual displacement principle while geometrical equations are derived using virtual force principle. In contrast to the approach of other authors, yield conditions and geometrical equations are described not only within finite elements, but also at the surfaces between elements. That helps to design the dual discrete mathematical models of the problems (21)-(26), in which the discontinuities of displacement velocities and the velocity of energy dissipation in the place of those discontinuities are estimated. The mathematical models (22), (24), (26), (29) and (32) of kinematic problem formulation are developed from sensible static formulations by Lagrange’s multiplier method. The modified mathematical models (27)-(29) are presented. In these models the equilibrium equations are eliminated or the geometrical equations are transformed into compatible equations of plastic stress velocities, in this way decreasing the number of equations and unknown values. The dependence of the numerical results (limit load) of the frame on the approximation degree of bending moments, as well as on the discretization method of yield conditions are illustrated. In table 1 the values of limit loading parameter F 0 and their error of calculation ΔF 0 (per cent, in comparison with the analytic solution F 0 = 0,4662M 0) are presented. They are given for the first and second order finite elements with linear and parabolic distribution of bending moments using different discrete yield conditions and a different number of finite elements. The numerical result shows, that the discretization of yield conditions by Bubnov-Galiorkin’s method gives the best accuracy and stable solutions. By discretizing yield conditions using the point’s collocation and collocation at the element, the accurancy of numerical results depends not only on the number of elements, but also on a more or less successful choice of finite elements net. Ribinės apkrovos analizės ir optimizacijos uždavinių formuluotės, panaudojant pusiausviruosius baigtinius elementus Santrauka. Sudaromi konstrukcijų ribinės apkrovos ir optimizacijos uždavinių dualūs diskretiniai matematiniai modeliai statine ir kinematine formuluote, panaudojant pusiausviruosius baigtinius elementus. Juose įvertinami galimi poslinkių greičių trūkiai ir energijos disipacijos greitis ne tik kūno tūryje, bet ir plastiniuose paviršiuose tarp baigtinių elementų. Remiantis statine teorema apie ribinę apkrovą [1, 2], pirmiausia sudaryti uždavinių bendri matematiniai modeliai (3) ir (7). Šių modelių diskretizacijai naudojami pusiausvirieji baigtiniai elementai ir įtempimų aproksimavimo funkcijos (9). Optimalumo kriterijumi pasirinkta išorinės apkrovos galingumo pastovumo sąlyga. Sudarytos pusiausvyros lygčių, takumo sǎlygų ir geometrinių lygčių diskretinės išraiškos baigtiniam elementui (10)-(12) ir konstrukcijos diskretiniam modeliui (14)-(17). Takumo sąlygos diskretizuojamos panaudojant klasikinius kolokacijų metodus: kolokacijų taške, kolokacijų srityje (elemente) ir Bubnovo-Galiorkino [11,12]. Diskretinio modelio pusiausvyros lygtys (14) sudaromos naudojant virtualių poslinkių principą, o geometrinės lygtys—virtualių jėgų principą. Skirtingai nei kitų autorių darbuose, takumo sąlygos ir geometrinės lygtys sudaromos ne tik baigtinių elementų vidui, bet ir jų išoriniams paviršiams. Tai ir leidžia sudaryti nagrinėjamų uždavinių diskretinius matematinius modelius (21)-(26), kuriuose įvertinami poslinkių greičių trūkiai ir energijos disipacijos greitis plastiniuose paviršiuse tarp baigtinių elementų. Uždavinių kinematinės formuluotės matematiniai modeliai (22), (24), (26), (29) ir (32) sudaromi iš atitinkamų statinių formuluočių Lagranžo daugiklių metodu. Taip pat pateikiami modifikuoti uždavinių matematiniai modeliai (27)-(29), kuriuose išeliminuotos pusiausvyros lygtys arba geometrinės lygtys pakeistos plastinių deformacijų greičių darnos lygtimis (27), taip sumažinant lygčių ir nežinomųjų skaičių. Rėmo pavyzdžiu iliustruojama skaitmeninių skaičiavimo rezultatų (ribinės apkrovos parametro) priklausomybė nuo lenkimo momentų aproksimavimo laipsnio ir nuo takumo sąlygų diskretizacijos būdo. 1 lentelėje pateiktos rėmo ribinės apkrovos parametro F 0 reikšmės ir jų procentinės paklaidos ΔF0 (palyginant su analitiniu sprendiniu F 0 = 0,4662M 0), gautos pirmos ir antros eilės baigtiniams elementams (su atitinkamai tiesiniu ir paraboliniu lenkimo momentų pasiskirstymu), diskretizuojant rygelius į 1, 2, 3 ir 4 baigtinius elementus. Skaičiavimo rezultatų analizė rodo, kad tiksliausi ir stabiliausi sprendiniai gaunami diskretizuojant takumo sąlygas Bubnovo-Galiorkino metodu. Diskretizuojant takumo sąlygas taškinės kolokacijos bei kolokacijos srityje būdu skaičiavimo rezultatų tikslumas priklauso ne tik nuo skaičiuojamojo tinklo tankio, bet ir nuo jo konfigūracijos daugiau ar mažiau sėkmingo pasirinkimo. Article in Russian. First Published Online: 26 Jul 2012